Sustaining rural livelihoods through participatory water governance: a review of community-driven water resource management models in East and Central Africa - Lema, Meserecordias Wilfred (Frontiers in Water, 2025)
This study reviews experiences across East and Central Africa testing community-driven arrangements for adaptively managing water resources according to local needs through participatory ownership and inclusive decision-making, empowering rural water users. An extensive database search identified 100 peer-reviewed publications related to community-driven water governance models, and the reviewed literature was analyzed and synthesized to develop an understanding of the topic. This research has revealed a total of nine common community-driven water resource management models. It was also established that these models possess several common aspects, namely, prioritizing high levels of community engagement and democratic governance and ensuring local representation in decision-making processes. However, these models were found to exhibit distinct differences across several dimensions in that some of them focused on broader management issues, i.e., water basin management, while others focused on specific water use issues, i.e., water access and distribution. Key characteristics for the success of various models were identified to be community engagement, local knowledge integration, inclusivity, collaboration among stakeholders, conflicts resolution mechanism, as well as funding and resources mobilization. Two models; Water User Associations and Integrated Community Structures emerged as relatively effective models in many contexts. Key lessons include empowering communities as stewards, investing in their capacities, fostering multisectoral collaboration, and formulating guidelines on equitable benefit-sharing.